1975
DOI: 10.1021/i360056a010
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanum Lead Manganite Catalyst for Carbon Monoxide and Propylene Oxidation

Abstract: The activity of single crystal lanthanum lead manganite (La0.7Pbo.3Mn03) was compared to Pt/Al203, Co304, and CuO under conditions important to automotive emission control. In simulated automotive exhaust ambients, the observed order of activity of fresh catalyts toward both CO and C3H6 oxidation was found in general to be: Pt/Al203 > Co304 > La0.7Pbo.3Mn03 > CuO. Pt/Al203 remained the most active of the materials throughout tests In which the susceptibility of catalysts to various modes of deactivation, namel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1976
1976
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…3 Given what we have discussed about electropositive cations promoting the oxidation and stabilization of precious metals, it is not surprising that small amounts of platinum were found to be present on these LaMnO 3 -and LaCoO 3 -based samples. 118 The influence of platinum in dilute amounts on the catalytic activity of the bulk oxides of interest was noted to be quite significant, with as little as 200 ppm Pt substantially improving their tolerance to sulfur poisoning, 7 but the nature of contaminant Pt was not immediately clear. X-ray photoelectron studies of Pt-containing La 0.7 Pb 0.3 MnO 3 , reported by researchers at Bell Laboratories, revealed the presence of Pt 4+ , and motivated the comparison of a bulk oxide containing Pt 4+ ions with a conventional supported metal.…”
Section: Perspectivementioning
confidence: 99%
“…3 Given what we have discussed about electropositive cations promoting the oxidation and stabilization of precious metals, it is not surprising that small amounts of platinum were found to be present on these LaMnO 3 -and LaCoO 3 -based samples. 118 The influence of platinum in dilute amounts on the catalytic activity of the bulk oxides of interest was noted to be quite significant, with as little as 200 ppm Pt substantially improving their tolerance to sulfur poisoning, 7 but the nature of contaminant Pt was not immediately clear. X-ray photoelectron studies of Pt-containing La 0.7 Pb 0.3 MnO 3 , reported by researchers at Bell Laboratories, revealed the presence of Pt 4+ , and motivated the comparison of a bulk oxide containing Pt 4+ ions with a conventional supported metal.…”
Section: Perspectivementioning
confidence: 99%
“…studies have revealed that co&4 is a more active catalyst for these reactions than are the other 3-d metal oxides (Yao, 1975;Dwyer, 1972;Shelef et al, 1968; Hofer et al, 1M, Katz et al, 1975;Krylov, 1970;Boreskov, 1973). Its activity h a been found to be comparable to that of the noble metals, such as Pt and Pd.…”
Section: Introductionmentioning
confidence: 99%
“…However, microwave irradiation enhances the diffusion of some species (Fe 3+ , in this case) selectively. There remain serious discussions about enhancement of solidstate diffusion by microwave irradiation, including whether it exists 12,13 or does not exist, 14 but from the result of this study, it seems to exist.…”
Section: Discussionmentioning
confidence: 75%